Chronic neuroinflammation and cognitive impairment following transient global cerebral ischemia: role of fractalkine/CX3CR1 signaling - Briones, Teresita L (BioMed Central, 2014)
Although neuroinflammation has been studied extensively in animal models of cerebral ischemia, their contrasting functions are still not completely understood. A major participant in neuroinflammation is microglia and microglial activation usually regulated by the chemokine CX3CL1 (fractalkine) and its receptor, CX3CR1. Here, we examined the involvement of CX3CR1 on ischemia-induced chronic neuroinflammation and cognitive function using small interfering RNA (siRNA). Forty adult male Wistar rats were included in the study and received either ischemia or sham surgery then were randomized to receive either CX3CR1 siRNA or scrambled RNA as control starting at 7 days after reperfusion. Behavioral testing commenced 28 days after siRNA delivery and all rats were euthanized after behavioral testing. Our data showed that: (i) transient global cerebral ischemia significantly decreased fractalkine/CX3CR1 signaling in the hippocampus; (ii) inhibition of CX3CR1 function exacerbated the ischemia-induced chronic increase in microglial activation and pro-inflammatory cytokine levels; (iii) inhibition of CX3CR1 function worsened ischemia-induced chronic cognitive impairment; (iv) inhibition of CX3CR1 function in sham rats resulted in increased IL-1β expression and impaired behavioral performance. However, no significant effect of CX3CR1 on ischemia-induced neurodegeneration was seen. The present study provides important insight to understanding the involvement of CX3CR1 in chronic neuroinflammation and cognitive impairment.